Stagnation, sammanbrott och social nyordning - rötterna till den ryska folkhälsokrisen (Sociologisk Forskning, 2000)
Stagnation, break-down and a new social order - the roots of the Russian public health crisisLong term trends of deteriorating health status in Soviet Union and Eastern Europe during the last two decades of communism were followed by a new crisis in health, after the collapse of its social system. In contrast, the perestroika period coincided with strongly improved public health. Explanations for the latest Russian health crisis are discussed. It is concluded that explanations based on poor medical care, excessive alcohol consumption or nutrional deprivation are, at best, insufficient. The collapse of the social system itself has lead to a narrowing of individual and collective decision latitudes; we speculate that historical factors, such as vulnerability of specific birth cohorts or segments of the population, may be part of the unexpected and very steep rise of mortality during the first half of the 1990s.